2006
DOI: 10.3130/jaabe.5.121
|View full text |Cite
|
Sign up to set email alerts
|

Walking Environments for the Visually Handicapped: Recognition of Geometric Model Spaces in a Laboratory

Abstract: In daily life it is not safe for visually handicapped people to walk alone as they can often fall victim to accidents or lose their way. In order to improve walking environments, it is important to show clearly how visually handicapped people recognize spaces and their position in spaces, and what the clues to recognition are.In this study, in order to clarify the relation between spatial cognition and space form, and the characteristics of search behavior, experiments are carried out using model spaces based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Previous findings support that environmental conditions help the visually handicapped navigate their surroundings (Kametani, Kishigami, & Chibana, 2006;Motlagh et al, 2009;Hwang, 2011). The findings suggested that smaller spaces and right-angle corners are less difficult for the vision impaired to recognize (Kametani et al, 2006) and tactile maps, handrails, and door signs contribute to reduced travel time (Hwang, 2011).…”
Section: Home Modification and Adjustment Of The Elderlymentioning
confidence: 70%
See 1 more Smart Citation
“…Previous findings support that environmental conditions help the visually handicapped navigate their surroundings (Kametani, Kishigami, & Chibana, 2006;Motlagh et al, 2009;Hwang, 2011). The findings suggested that smaller spaces and right-angle corners are less difficult for the vision impaired to recognize (Kametani et al, 2006) and tactile maps, handrails, and door signs contribute to reduced travel time (Hwang, 2011).…”
Section: Home Modification and Adjustment Of The Elderlymentioning
confidence: 70%
“…The findings suggested that smaller spaces and right-angle corners are less difficult for the vision impaired to recognize (Kametani et al, 2006) and tactile maps, handrails, and door signs contribute to reduced travel time (Hwang, 2011).…”
Section: Home Modification and Adjustment Of The Elderlymentioning
confidence: 97%
“…Some studies have investigated environmental conditions with the goal of helping the visually handicapped navigate their surroundings (Kametani, Kishigami, & Chibana, 2006a, 2006bMotlagh et al, 2009;Hwang, 2011). The findings suggested that smaller spaces and right-angle corners are less difficult for the vision impaired to recognize (Kametani, et al, 2006a).…”
Section: Home Modification and Needs Of The Vision Impairedmentioning
confidence: 99%